Regional applications of observations in the eastern Pacific: Western South America - Takahashi, Ken (2014)
En: Report of the Tropical Pacific Observing System 2020 Workshop (TPOS 2020), Volume II – White Papers, n. 8a, San Diego, United States, January 27-30, 2014, Scripps Institution of Oceanography, p. 171-205. OOPS (Ocean Observations Panel for Climate)